Teachers' Perception of Task-Based Language Teaching in Teaching English Writing at Indonesian Secondary School - Nur Faizah Akidah; Haryanto Atmowardoyo; Iskandar Iskandar (Fakultas Sastra - Universitas Muslim Indonesia, 2024)
This study investigates teachers' perceptions of Task-Based Language Teaching (TBLT) in the context of teaching English writing at Indonesian secondary schools. Through semi-structured interviews with three English teachers who working in SMA Insan Cendekia Seych Yusuf, the research revealed a complex interplay of beliefs regarding the effectiveness and challenges of implementing TBLT. The findings indicated that while teachers generally recognize the potential of TBLT to enhance student engagement and improve writing skills, significant barriers remain. These include students' readiness for collaborative tasks, institutional constraints related to an exam-oriented curriculum, and the need for professional development to equip teachers with the necessary skills for effective TBLT implementation. The study highlights the importance of addressing these challenges through targeted training and curriculum alignment to facilitate the successful integration of TBLT in language education. Ultimately, the insights gained contribute to the growing body of literature on TBLT and underscore the need for further research to explore effective strategies for overcoming barriers to its implementation.